Analisis Indeks Produktivitas Tanah Untuk Meningkatkan Pengembangan Kacang Tanah di Desa Cimaung, Banten - Riskawati Riskawati; Latief Mahir Rahman (Median : Jurnal Ilmu Ilmu Eksakta, 2023)
Soil conditions need to be evaluated to determine the potential productivity index of the land. One of the food crops that has long been developed by farmers in Cimaung Village, Cikeusal District is peanuts. The decline in soil conditions is caused by more intensive land management, so it is necessary to analyze the potential productivity index of the soil. This study aims to determine the potential productivity index of the soil for peanut land use which can display soil productivity before burial. This research was conducted in a farmer's garden, in Cimaung Village, Cikeusal District, Serang Regency, Banten Province (Coordinates 6o12'14'' S and 106o11'52'' E). The magnification of the potential index of soil productivity used the modified Storie (1987) method, which was adjusted to the research location using several soil property parameters, which effective depth of soil, soil texture, permeability, C-organic, pH, N-total, P and CEC. The results showed that the potential productivity index of the resulting soil was in class IV with a value of 28% in the bad category with the limiting factor "having limitations on locational commodities". Suitability limitations are influenced by soil fertility and soil acidity, so it is necessary for wise land management managers to make improvements in the management of fertilization using organic matter.